Gastronomy as a new way of exploring tourism destinations, particularly in the case of Budapest - Sziva, Ivett; Simon, Judit; Szakály, Orsolya (Marketing & Menedzsment, 2017)
THE AIMS OF THE PAPER Budapest is already among the rising stars of the European capitals. Its reasons can be commonly known: the changing motivations of cultural tourism, among which gastronomy, as well as design can be mentioned, and the Hungarian capital can hold both important values. Budapest was nominated as a Creative City of Design by UNESCO and has become the favorite place for different gastronomy bloggers in the recent years. Gastronomy has an important role in tourism. The culture of food and beverage has come in the spotlight through gastronomic tourism due to nations and the gastronomic features of destinations. Millions of tourists return to a destination to taste the traditional flavors or to feel the place and discover the destination. After discussing the cultural, creative and gastronomy (or / and culinary tourism) of Budapest, the main issue is the cultural tourism of Budapest, followed by the results of a new niche research regarding the motivations of international cultural tourists arriving in Hungary, and Budapest. Our main task is to realize how tourists perceive Budapest and to leam what are the main activities, which arise their interest. METHODOLOGY In our quantitative research 307 international travelers were asked about their attitudes regarding lifestyle, activities during their travels, and their main motivation to visit Budapest, with a specific focus of gastronomy, as an important new trend of cultural and creative tourism, and a deep understanding of culture during visiting a destination. MOST IMPORTANT RESULTS According to the results, the gastronomy of Budapest is among the most important attractions as well as the activities taken by the tourists, though the local flavors are not as popular as expected. RECOMMENDATIONS There is a great revolution of gastronomy in Budapest, even with renewing the Hungarian specialties, but more communication and further product development are needed to make these changes accepted by the market.